Comparative analysis on the effect of low-thermal plasma dissection device (PEAK PlasmaBlade) vs conventional electrosurgery in post-bariatric abdominoplasty: A retrospective randomised clinical study - Schlosshauer, Torsten; Kiehlmann, Marcus; Riener, Marc-Oliver; Sader, Robert; Rieger, Ulrich M. (International Wound Journal, 2019)
Post-bariatric patients undergoing abdominoplasty have a relatively high risk of complications due to residual obesity and major comorbidities. Also, conventional electrosurgery and the associated thermal tissue damage may compromise outcomes. This retrospective randomised clinical study evaluated the effect of low-thermal plasma dissection device (PEAK [pulsed electron avalanche knife] PlasmaBlade) in comparison with conventional electrosurgery. A total of 52 post-bariatric patients undergoing abdominoplasty were randomised to PEAK PlasmaBlade (n = 26) and to monopolar electrosurgery (n = 26). Wounds of 20 patients per group were examined histologically for acute thermal injury depth. In PEAK PlasmaBlade incisions, acute thermal damage was significantly reduced compared with standard of care (40% vs 75%; P = .035). Also, acute thermal injury depth from PEAK PlasmaBlade was less than that from electrosurgery (2780 mu m vs 4090 mu m). Significantly less total complication rate (30.8% vs 69.2%; P = .012) was found by PEAK PlasmaBlade compared with electrosurgery. Moreover, the PEAK PlasmaBlade showed less than half as many wound healing problems (19.2% vs 46.2%; P = .075), far fewer secondary bleeding (7.7% vs 30.8%; P = .075), and no seroma compared with four seroma with the standard of care (0% vs 15.4%; P = .11). PEAK PlasmaBlade appears to be superior to traditional monopolar electrosurgery for post-bariatric abdominoplasty, because it demonstrated significantly less tissue damage, less total complication rate, and fewer postoperative seroma resulting in faster wound healing.
CRIS-Team WoS Importer:2019-10-04